Personality-Related Determinants of Physical Activity Among Polish and Spanish Physical Education Students - Gacek, Maria; Kosiba, Grażyna; Wojtowicz, Agnieszka; López Sánchez, Guillermo F.; Szalewski, Jacek (Frontiers in Psychology, 2022)
We aimed to analyze personality-related determinants of physical activity among Polish and Spanish physical education (PE) students. The study was conducted among 219 Polish and 280 Spanish PE students, using the International Physical Activity Questionnaire (IPAQ) and the NEO-FFI Personality Inventory. Compared with Spanish PE students, their Polish counterparts are characterized by a higher level of extraversion and conscientiousness and a lower level of neuroticism. The level of total physical activity for all students was 8,697.21 METs, and this value was higher among Polish students. Among Polish and Spanish PE students, the level of total, vigorous, and moderate physical activity increased along with the increase in extraversion, while a decrease occurred along with the increase in neuroticism. The level of each domain of physical activity also increased in line with the intensification of student conscientiousness. In moderation analyses, it was shown that the home country of students may be considered a moderator of the relationship between conscientiousness and total exercise in such a way that the physical activity increased along with the increase in conscientiousness only among the Polish students. In addition, the country is a moderator of the correlation between moderate physical activity and neuroticism (p = 0.031), openness (p = 0.049), and conscientiousness (p = 0.019), with moderate activity only decreasing among Polish students and increasing along with the increase in openness and conscientiousness. Positive correlations among physical activity, extraversion, and conscientiousness, as well as negative ones with neuroticism, were demonstrated among Polish and Spanish students, and also the moderating impact of the country on the correlation between personality-related dimensions and physical activity.